STRATEGI MENGOPTIMALKAN TOLERANSI ANTAR UMAT BERAGAMA - Wigunadika I Wayan Sapta (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2017)
Indonesia is a nation inhabited by people with diverse religious, ethnic, and social backgrounds. Plurality is an indisputable reality in this archipelago. On the one hand, this pluralism becomes the social capital of nation-building, and on the other hand the latent potential of social conflict. Humans are both indiviudu creatures as well as social beings. As social beings of course human beings are required to be able to interact with other individuals in order to meet their needs. In living a social life in society, an individual will be faced with groups of different colors with him one of which is the difference of religion. Live his social life can not be denied there will be friction-friction that will occur between groups of people, both related to race and religion. In order to maintain unity and unity in society it is necessary to respect each other and respect each other, so that friction-friction that can lead to disputes can be avoided. Communities are also required to keep each other’s rights and obligations between them from each other. All religions come from God Almighty who is revealed through His revelation or holy word to glorify human life. Through His holy teachings, it is hoped that human beings will become human beings who possess noble character. As long as the doctrine which is practiced by man does not deviate from the path of truth, then the differences that exist in every religion need not be disputed. By living side by side without questioning religious differences, it actually shows the implementation of the teachings of religion itself. Religious people are human beings capable of dampening any emotional upheaval arising from differences in patterns of religious life that differ from individual to individual, so violence in the name of religion can be avoided. Is not the flowers of the garden looks beautiful precisely because the colors of different flowers. Differences are not a barrier to knit the ropes of the brotherhood and build a harmony of life.Keywords: Optimizing, Tolerance, Interfaith People